2020
DOI: 10.1088/1755-1315/419/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis the effects of soil-structure interaction on the seismic behaviours of a 5-stories reinforced concrete building with basements

Abstract: The paper presents analysis results of structural behaviour with and without soil-structure interaction on a five-story reinforced concrete building with basements due to seismic loads. Two numbers of basements were considered namely the building with one basement floor (M1 model) and two basement floors (M2 model). Each of the M1 and M2 model has three variations with and without the soil structure interaction namely the model with the fixed supports (MJ1 and MJ2 models), the model with solid element of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Numerous studies have been conducted in the past decades to understand and analyze the seismic performance of structures with subterranean levels [13][14][15][16][17][18][19][20][21]. In the study done by El Ganainy and El Naggar [17], the seismic performance of moment-resisting frame steel buildings with multiple underground stories and varying building heights was evaluated through a 3D nonlinear finite element model (FEM) by considering the seismic hazard of Vancouver, Canada, and the use of BNWF model to simulate the essential aspects of the nonlinear behavior of the foundation and side soil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have been conducted in the past decades to understand and analyze the seismic performance of structures with subterranean levels [13][14][15][16][17][18][19][20][21]. In the study done by El Ganainy and El Naggar [17], the seismic performance of moment-resisting frame steel buildings with multiple underground stories and varying building heights was evaluated through a 3D nonlinear finite element model (FEM) by considering the seismic hazard of Vancouver, Canada, and the use of BNWF model to simulate the essential aspects of the nonlinear behavior of the foundation and side soil.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that underground structure cracking should be included in the building's structural analyses and that foundation movement should be explicitly considered for soil class D and softer. Recently, Sudarsana et al [21] showed that basement floors' addition could minimize the roof-floor displacement, the structure's natural fundamental period, and axial column forces when considering SSI effects. Moreover, the effects of SSI on the dynamic response of other types of structures have also been assessed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation